Smart water quality monitoring and purification system development for domestic application - Hossain, Md Thamid; Hossain, Tasbiah Binte; Haque, Shafkat; Fida, MD Saif (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.